Influence of Entrepreneurial Orientation on Firms Performance: Evidence from Small and Medium Enterprises in Nigeria - Ibrahim, Abbas Umar; Abu, Martins Mustapha (International Journal of Economics and Financial Issues, 2020)
Entrepreneurship has emerged as promising new solutions to solve societal problems. This study seeks is to analyses how entrepreneurial orientation i.e. proactiveness, competitive aggressiveness autonomy, innovation, and risk-taking influence firms’ performance in Abuja. To fulfil this purpose, survey research design and a theoretical framework were developed depicting the different entrepreneurial orientations and firm performance in its context. Sampling technique of simple random was adopted in which only one hundred and ten (110) SMEs in Abuja responded to the survey questionnaire and a total of ninety-seven (97) valid responses were judged to be appropriate. The descriptive statistics and as well as inferential statistical tool was used to analyses the data. It was revealed that proactiveness, risk-taking and autonomy are positive and significantly related to business performance while, competitiveness was positive but insignificant. It is recommended that similar studies should be replicated to validate this result. Keywords: Entrepreneurial orientation; Firms Performance; Technology-based SMEs JEL Classifications: L25, L26 DOI: https://doi.org/10.32479/ijefi.9126